2023
DOI: 10.1021/acs.inorgchem.3c00132
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Adsorption Performance for Poisonous Methylene Blue through the Amino Functionalization of Metal–Organic Frameworks

Abstract: Amino (−NH2)-functionalized metal–organic frameworks (MOFs) are widely applied to improve the properties of materials owing to the rich host–guest chemical properties of amino groups. In this work, the amino-functionalization strategy was thus employed to improve the sorption performance of methylene blue (MB). The introduction of −NH2 groups in AOBTC-Zn did not reduce the pore size of the framework but rather modulated and optimized the host–guest interactions of MOFs. The MB+ sorption result was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Instead, it modulates and optimizes the MOF’s chemical interaction. For instance, Jing et al reported the application of amino-functionalized MOF (NH 2 -AOBTC-Zn) to remove toxic MnB from water. The results showed that grafting of the amino group has significantly enhanced the adsorption capacity of NH 2 -AOBTC-Zn toward MnB, resulting in an adsorption capacity of 1623 mg/g, compared to the mere 204 mg/g absorbed by pristine AOBTC-Zn.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it modulates and optimizes the MOF’s chemical interaction. For instance, Jing et al reported the application of amino-functionalized MOF (NH 2 -AOBTC-Zn) to remove toxic MnB from water. The results showed that grafting of the amino group has significantly enhanced the adsorption capacity of NH 2 -AOBTC-Zn toward MnB, resulting in an adsorption capacity of 1623 mg/g, compared to the mere 204 mg/g absorbed by pristine AOBTC-Zn.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Various adsorbent materials have been employed for dye capture, such as carbon materials, 11,12 biopolymers, 13,14 metal-based materials, 15,16 organic polymers and their composites, 17–19 including metal–organic frameworks (MOFs). 20–32 MOFs can be tailored based on the precursor metal salts/ligand moiety and by post-synthetic modification to neutral or charged (cationic/anionic) MOFs, and most commonly used ionic dyes in the industry can be readily separated by the ion-exchange process using ionic MOFs. 33–39…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption is considered to be one of the most promising methods to address water pollution, owing to the characteristics of low energy consumption, eco-friendliness, and cost-effectiveness . Traditional adsorbents, such as zeolites, clay, mesoporous carbon, and metals oxides, often suffer from slow adsorption kinetics, low adsorption selectivity, and capacities, which stems from their simple composition and lack of structural and functional tunability. , To achieve better adsorption performance for uranium, adsorbents with structural and functional tunability are highly desired, and adsorbent design with multiple factors should be considered, including surface area, porosity, and amount of adsorption sites. Bearing this in mind, metal–organic frameworks (MOFs), a kind of crystalline hybrid porous material with a large surface area, densely populated chelating groups, and tunable pore structures, have been developed . The precisely designable and tailorable structures and components in MOFs are convenient to realize high performance in uranium extraction. Amidoxime groups can be purposefully incorporated into UiO-66-NH-(AO) by a postsynthetic strategy, which showed good selectivity for uranium even in the presence of high concentrations of VO 2 2+ , Fe 3+ , Mg 2+ , Ca 2+ , and Zr 4+ .…”
Section: Introductionmentioning
confidence: 99%